GPX3 promotes cisplatin resistance in TNBC by manipulating ROS-TGFB1-ZEB2 - Qingyi Hu; Qianzhi Chen; Wen Yang; Anwen Ren; Jie Tan; Tao Huang (Cell Communication and Signaling)
Abstract Background Due to the lack of effective targeted therapies and the high likelihood of acquired resistance, triple-negative breast cancer (TNBC) remains one of the deadliest cancers affecting women globally. Investigating the mechanism underlying TNBC’s resistance to platinum-based chemotherapy and identifying new therapeutic targets are urgent priorities. Methods The expression level of GPX3, cisplatin sensitivity, and ROS production were compared across three TNBC cell lines to elucidate the relationship between GPX3 and platinum resistance. RNA sequencing and bioinformatics analyses of GPX3 knockdown cells revealed its regulation of stress-related signaling pathways and TGFB1. The regulation of TGFB1 by GPX3 was further investigated using Western blotting, RNA interference, confocal microscopy, and inhibitor treatments. The correlation between the expression level of GPX3, TGFB1, and ZEB2 was analyzed using breast cancer microarrays and the TCGA database. The effect of GPX3 on platinum sensitivity in TNBC was studied using a mouse xenograft model. Results GPX3 expression was upregulated in more invasive TNBC cells, promoting resistance to cisplatin-based chemotherapy. RNA sequencing revealed that the deletion of GPX3 resulted in a decrease in gene expression patterns associated with pro-tumor signaling pathways. Validation experiments confirmed that the upregulation of TGFB1 in acquired cisplatin resistance is highly dependent on GPX3. Further investigation revealed that the TGFB1-ZEB2 axis mediated platinum resistance and metastasis through epithelial-mesenchymal transition (EMT). Additionally, platinum treatment increased GPX3 and TGFB1 expression and secretion, and their depletion enhanced platinum sensitivity in TNBC cells. We identified the GPX3-TGFB1-ZEB2 regulatory axis and found a positive correlation in the expression of all three in clinical samples. Our study also demonstrated that GPX3 knockdown inhibited TNBC tumor growth in platinum-treated mouse models. Conclusions This study reveals the signaling pathway mediated by GPX3-TGFB1-ZEB2 and its role in acquired platinum resistance and EMT in TNBC. Our findings suggest that GPX3 is a promising biomarker and potential therapeutic target for the diagnosis, treatment, and prognosis of high-risk TNBC patients.